Kingdom of Bahrain : Detailed Assessment on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessment on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Bahrain. The assessment was based on the 2003 Financial Action Task Force (FATF) 40 Recommendations. The assessment identifies recommendations on how certain aspects of the system could be strengthened. The assessment reveals that the AML/CFT effort is taken seriously in Bahrain and the Kingdom has worked hard over the past few years to implement an extensive AML framework to address the risk of money laundering.